Social Status, Inflation Uncertainty, and Growth in a Cash-in-Advance Economy - Liutang Gong (Taylor & Francis Journals, 2008)
In a stochastic monetary model with the cash-in-advance constraint and the social-status concern, this paper studies the effects of inflation and inflation variability on growth. It is shown that the Tobin effect still holds under deterministic monetary growth. The effect of inflation on growth, however, is ambiguous under stochastic monetary growth: the effect is positive when an agent's desire for social status is relatively strong and negative when this desire is relatively weak. It is also found that inflation variability always stimulates growth.